Economic and Legal Aspects of Consumer Right Protection in Tourism - ADAMENKO, Alla Petrovna; ANANYEVA, Anna Anatolyevna; ZARAPINA, Lidia Vladimirovna; TSELOVALNIKOVA, Irina Yuryevna; SEMENOVA, Julia Alexandrovna (Journal of Environmental Management and Tourism, 2021)
This article is devoted to economic and social aspects of consumer right protection in tourism. It has been established that the consumer protection is an important element of social protection policy. More intensive care about this subject improves consumer safety in tourism as well as increases consumer interest in it. Moreover, awareness of tourists can result in elimination of certain problems and inform tourists about their rights, thus enhancing their safety and satisfaction upon consumption of tourism products or other services. It has been proved that peculiar attention in this case should include moral damages. Therefore, possibility to indemnify moral damages caused by property damage is stipulated by special tourism legislation.